Modal Manusia dan Kaitannya dengan Kinerja: Suatu Kajian terhadap Gudang Manufaktur Berlisensi di Semenanjung Malaysia - Ramli, Azhari; Poespowidjojo, Donny Abdul Latief; Shakir, Khairunnisak Ahmad (Jurnal Kajian Manajemen Bisnis, 2014)
Firm resources are fundamental drivers of performance. It can be classified into three categories: physical capital, organizational capital and human capital. Human capital has been considered a major asset to warehouse operations, but has not been tested empirically. A study was conducted to test the relationship between human capital and warehousing performance has been conducted on the Licensed Manufacturing Warehouse (LMW) in Peninsular Malaysia. There are 1958 manufactureres with LMW and 800 were randomly selected. During data collection, this study received 107 responses and 102 responses were used. The result showed that, human capital has a positive relationship and significantly influential on the performance of warehousing. This study has provided information that any additional value to human capital can lead to better performance. For the future, studies should be done on the relationship between other resources to the performance of organizations. Such studies can help to increase knowledge about the phenomenon of the relationship between resources and performance.